2002
DOI: 10.1556/amicr.49.2002.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal pneumonia caused by Trichomonas vaginalis

Abstract: The authors present two cases of newborn babies infected by Trichomonas vaginalis (hereafter referred to as T. vaginalis) and suffering from severe congenital breathing difficulties and needing artificial respiration. Microscopic examination of the tracheal discharge revealed characteristically moving, flagellated, pear-shaped unicellular organisms. Cultures on CPLM medium proved the presence of T. vaginalis. During pregnancy the mothers' clinical status was negative and both of them mentioned leukorrhoea of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…Approximately 50% of infections present with non-typical symptoms ranging from vaginitis, cervicitis and vulvitis in women, to urethritis, prostatitis and pruritis in men [12,13]. Neonatal ocular and respiratory infections have also been described in neonates of infected mothers [14,15]. Chronic infections have been associated with pre-term birth and low birth-weight neonates, cervical cancer and increased HIV transmission amongst the most alarming [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 50% of infections present with non-typical symptoms ranging from vaginitis, cervicitis and vulvitis in women, to urethritis, prostatitis and pruritis in men [12,13]. Neonatal ocular and respiratory infections have also been described in neonates of infected mothers [14,15]. Chronic infections have been associated with pre-term birth and low birth-weight neonates, cervical cancer and increased HIV transmission amongst the most alarming [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, other trichomonad species have also been identified in human lungs by molecular means. These include T. vaginalis (4,15,18), P. hominis (8), and a new Tetratrichomonas species that had not previously been reported as a human parasite (9). Thus, the presence of these protozoa in the human respiratory tract is not unusual, and we have recently shown that trichomonads are frequently found in lungs of immunocompromised patients in association with Pneumocystis organisms (5).…”
Section: Case Reportmentioning
confidence: 97%
“…T. vaginalis is considered the only pathogenic trichomonad and causes infection mainly of the genitourinary tract. However, the presence of this protozoan parasite in the human respiratory tract has been reported previously (3)(4)(5). In addition, with more sensitive molecular methods, other trichomonads, namely, Trichomonas tenax, Pentatrichomonas hominis, Tritrichomonas foetus, Tetratrichomonas gallinarum, and a new Tetratrichomonas species, have been found in a number of cases in the respiratory tracts of humans (6,7).…”
mentioning
confidence: 99%
“…As was shown in our case, mechanical exposure of healthy conjunctivae to vaginal secretions harboring T. vaginalis parasites led to conjunctival infection in an adult man. In addition, rare cases of respiratory tract infections in infants born to mothers with histories of genital trichomoniasis indicate the same route of transmission (4,5). The recent molecular detection of T. vaginalis in pharyngeal specimens from three HIV-infected men with histories of orogenital sexual activity (10) highlights the need for further research to unravel the transmission dynamics and pathogenesis of extragenital trichomoniasis.…”
mentioning
confidence: 99%